Students’ Perception Of Sleman Geschool Web-Based Learning Application In Junior High School - Denna Ananda Yushinta; Nur Hidayanto Pancoro Setyo Putro (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aimed to find out students’ perception of Sleman GeSchool Web-Based Learning Application in junior high school. This study was classified into qualitative research. This research study took place on one of the junior high schools in Sleman. The subjects of this study were the eighth graders students consisting of 5 boys and 5 girls. Observations, interviews and documentations were used to collect the data. The qualitative data were analysed using descriptive analysis.The result of the study showed that the Sleman GeSchool Web-Based Learning Application is supporting students in learning English because the material is interesting and easily accessible as well as good visualization of material explanations and practice questions that can make students learn easily. However, from the many things that support the students, students consider that there are still shortcomings in the Sleman GeSchool Web-Based Learning Application, for example, the lack of space to upload assignments in the form of essay and the difficulty of the platform to access when there is no internet network.